A qualitative metasynthesis of stigma in women living with HIV in the United States - Sadie Sommer; Julie Barroso (BMC, 2023)
Abstract Our goal was to synthesize qualitative studies on HIV-related stigma as experienced by women living with HIV (WLWH) in the U.S. Qualitative metasynthesis techniques as developed by Sandelowski et al. (Res Nurs Health 30(1):99-111, 2007) were used to integrate and update findings on stigma in WLWH in the U.S. in 43 reports of qualitative studies conducted between 2004 and 2023 with 1118 participants. Developed themes explored a collective narrative of women first surviving the intersectionality of multiple sources of stigma, discovering non-linear pathways to transcend their stigma, and finally experiencing resilience through their transcendence of stigma. While this metasynthesis revealed similarities to an earlier metasynthesis in the ubiquity and persistence of stigma, they differ primarily in women's abilities to find agency in managing and opposing their stigma. This cognitive reframing of their stigma helped women to redefine stigma as ignorance and move towards a more positive assessment of the self. In doing so, they separated themselves from their stigma and the damaging effects of it. Findings from this metasynthesis may serve as a useful tool for the development of stigma reduction interventions specific to the needs and experiences of WLWH in the U.S.